Teacher’s Strategies in Teaching Auxiliary Verbs at SMP Negeri 1 Mamasa - Asglorya, Desri Novia; Muliati, A.; G, Hasriani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This research aims to find out the teaching strategies applied by the teacher in teaching auxiliary verbs and also to know the students’ level of mastery of auxiliary verbs. The type of this research is descriptive with quantitative and qualitative data. The result of this research is based on the qualitative data the teacher at SMP Negeri 1 Mamasa applied a few strategies in teaching auxiliary verbs, they are problem-based learning, discovery learning or inquiry learning, and project-based learning. Besides that, based on the quantitative data, the students’ level of mastery is in the A2 level, 45% of the students are in the basic A2, 42,5% students are in the high basic A2, and 12,5 % in pre-intermediate B1 level of mastery it can be concluded that the students level of mastery of auxiliary verbs, most of the grade eight students at SMP Negeri 1 Mamasa still did not understand the auxiliary verbs well.